Ahorro De Espacio - Atienza, Geralyn Therese B.; De Guzman, Nicole Ann B.; De Vera, Veronica L.; Dungca, Jessica Pauline D.; Ituralde, Danah Royce S.; Lagua, Mary Chris M.; Mata, Michelle Anne R. and Morong, Andrea Joyce R. 4 0 16; 5
u
Feasibility Study: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2